PENGARUH BIAYA OPERASIONAL PENDIDIKAN TERHADAP OUTPUT PENDIDIKAN GURU SMK SE-KABUPATEN GRESIK DENGAN PRODUKTIVITAS KERJA SEBAGAI VARIABEL MODERASI - Rohmawati, Rohmawati (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
This study aims to (1) analyze the influence of education operational costs on educational output at Vocational High School/ SMK in Gresik regency, (2) analyze the effect of education operational costs on educational output with teachers work productivity as a moderating variable at SMK in Gresik regency. This research is an explanatory research with a quantitative approach. The population in this research are vocational high schools (SMK) at Gresik regency. The sampling technique used was purposive sampling. The data collection techniques which used are documentation and interview techniques. While the method of analysis that used is descriptive statistical analysis techniques, statistical analysis techniques infrensial regression with SPSS. The results showed that the education operational cost does not affect the output of education at SMK in Gresik and education operational cost does not affect the educational output with teachers work productivity as moderating variable. Teachers work productivity less can be used as a moderator variable or can not be used as independent variables that have an influence on educational output variables